A case of initiator-leadership and follower-leadership - Alvesson, Mats, 1956- (SAGE knowledge. Cases., 2016)
This case study presents a historical overview of a Swedish computer consultancy company's leadership model, including the founders and public figures that contributed to the company's growth. This case helps the reader to understand the relationship between organizational culture and leadership.